Combining sterols with stable carbon isotope as indicators for assessing the organic matter sources and primary productivity evolution in the coastal areas of the East China Sea. (1st July 2021) - Wang, Yueqi; Song, Jinming; Duan, Liqin; Yuan, Huamao; Li, Xuegang; Li, Ning; Zhang, Qian; Liu, Jin; Ren, Chengzhe
Abstract: To identify the sedimentary organic matter (OM) sources and reconstruct primary productivity evolution process in the coastal areas of the East China Sea (ECS), carbon, nitrogen and carbon stable isotope (δ 13 C) combined with sterols were studied in the surface and core sediments. The quantitative calculations of δ 13 C model and characteristic sterols suggested that the OM is derived from mixed marine and terrestrial inputs. Sinking marine phytoplankton was the dominant marine OM (MOM) source, with the average MOM proportion calculated by two end-member model of δ 13 C and characteristic sterol analysis of 73% and 62%, respectively. Terrestrial organic matter (TOM) displayed a decreasing trend seaward, attributed to the Changjiang River input as the dominant terrestrial source pathway. The decreased proportion of TOM with age in the core sediment was mainly controlled by the fluctuating changes of freshwater and sediment influxes of the Changjiang River. The sum content of epi-brassicasterol and dinosterol increased with age in recent 30 years, suggesting the increasing phytoplankton productivity. Enhanced anthropogenic nutrient inputs from the Changjiang River as well as the incremental nutrient supplement from the deep waters of the coastal upwelling area aggravated the phytoplankton blooms. Besides, the increasing ratio of epi-brassicasterol to dinosterol contents (B/D ratio) with age revealed the increasing diatom productivity relative to dinoflagellate productivity. This variation was mostly attributed to the natural forcing of the increased nutrient supplement from intensified coastal upwelling in the Zhejiang coastal mud area. Highlights: Marine organic matter input was the dominant source in the sediments. Terrestrial organic matter was mainly controlled by the Changjiang River input. The phytoplankton productivity increased during the past 30 years. Increased diatoms compared with dinoflagellates was controlled by natural forcing.